Human Fungal Pathogens - Kurzai, Oliver; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Whereas plant and insect infections are commonly caused by fungi, only a small minority of the vast diversity of fungal species is pathogenic to humans. Despite this, fungal infections cause considerable morbidity and mortality worldwide. This volume is dedicated to the biology, clinical presentation and management of invasive fungal infections. Major pathogenic fungi are introduced by world-leading experts and the basic principles of fungal virulence are reviewed in the light of new results and experimental technologies that offer unprecedented insights into invasive infections caused by Aspergillus, Candida, Cryptococcus, Pneumocystis and Mucorales. In parallel, the clinical presentation of invasive fungal infections and current approaches to their diagnosis and treatment are summarized to provide an overview of human pathogenic fungi, linking pathogen biology to the clinical presentation of disease.
From Commensal to Pathogen: Candida albicans -- Aspergillus fumigatus: Saprotroph to Pathogen -- Systems Biology Approaches to Understand and Predict Fungal Virulence -- Receptor-Ligand Interactions in Fungal Infections -- Macrophages in the Immune Response against Cryptococcus -- T Cell Responses in Fungal Infections -- Molecular Mechanisms of Histoplasma Pathogenesis -- Visualizing Immune Responses in Fungal Infections – Established and Novel Methods -- Mucosal Immunology in Candida albicans Infection -- Invasive Aspergillosis in the Intensive Care Unit -- Molecular Epidemiology of Pneumocystis Outbreaks -- Infections Caused by Mucorales -- Diagnostics of Fungal Infections -- Therapeutic Strategies in Fungal Infections -- Antifungal Pharmacokinetics.
Keywords: Medical microbiology; Immunology; Allergy; Cell biology; Microbiology; Microbial genetics; Microbial genomics; Medical Microbiology; Immunology; Allergology; Cell Biology; Eukaryotic Microbiology; Microbial Genetics and Genomics